The Total phenolic content, total flavonoid content and in vitro antioxidant activities measured by the FRAP, ABTS, DPPH and ORAC assays of Sri Lankan black and green tea (Camellia sinensis) infusions - Thennakoon, T. M. E. S.; Abeysinghe, P. D.; Ranasinghe, P.; Pathirana, R. N.; White, Alex; Fernando, W. G. Dilantha; Abeysinghe, S.; Premakumara, S. (Food Biology, 2022)
Tea is one of the most ancient and popular therapeutic beverages consumed by people all over the world. It is made from the leaves and buds of the plant “Camellia sinensis”. Tea is cultivated in more than thirty countries around the world as a plantation crop. In the present study, thirty tea samples of 20 black and 10 green tea manufactured in Sri Lanka were screened for antioxidant activities. Black tea samples were obtained from the three main geographical regions low (Dust (I), BOPF, BOPI, OPI, Pekoe), mid (Dust (I), Dust, BOPF Local, BOPI, BOP, OPI, Pekoe) and up (Dust, BOPF, BOP, FBOP, FBOPI, OPA, OPI, Pekoe) country of Sri Lanka. Green tea samples are manufactured by two different processing methods; panning (Ceylon GT Chunmee (I), Ceylon GT Chunmee (II), Ceylon GT Fanning’s, Ceylon GT Gun Powder (GP) (Extra Spl), Hyson, OPA green tea Ceylon GT Special Hyson) and steaming (Ceylon Sencha OPA, Ceylon Tencha, Cut Twist Curl (CTC) green tea) were used in the investigation. Total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities using ABTS, FRAP, DPPH and, ORAC assays were determined for each tea infusion. According to the results, phenolic content was higher in green tea than that of black tea and flavonoid content was lower in green tea than in black tea. Results of all antioxidants assays showed higher values for green tea than black tea. Neither the geographic area from which the samples of black tea came nor the method of preparation of green tea showed any significant differences in the activities. The results of the study have shown that Sri Lankan tea has compounds with antioxidant activities. Therefore, Sri Lankan tea can be used as a therapeutic beverage and a possibility to use the tea for producing antioxidant drugs through extraction and isolation processes.